1996
DOI: 10.1128/iai.64.12.4922-4927.1996
|View full text |Cite
|
Sign up to set email alerts
|

Antiendotoxin activity of cationic peptide antimicrobial agents

Abstract: The endotoxin from gram-negative bacteria consists of a molecule lipopolysaccharide (LPS) which can be shed by bacteria during antimicrobial therapy. A resulting syndrome, endotoxic shock, is a leading cause of death in the developed world. Thus, there is great interest in the development of antimicrobial agents which can reverse rather than promote sepsis, especially given the recent disappointing clinical performance of antiendotoxin therapies. We describe here two small cationic peptides, MBI-27 and MBI-28,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(100 citation statements)
references
References 37 publications
2
96
1
1
Order By: Relevance
“…In comparison, synthetic DEFB3 did not reduce LPSmediated activation of MAPK, albeit DEFB2 (i.e., hBD2) is known to have a similar effect as DEFB123 (42). The inhibition of LPS and the blocking of TNF-␣ was also reported for the ␣-helical peptide MBI-28 (43), which is in the same MW range. In addition, the structurally unrelated cathelicidin CAP18/LL-37 shows similar behavior (33).…”
Section: Discussionmentioning
confidence: 79%
“…In comparison, synthetic DEFB3 did not reduce LPSmediated activation of MAPK, albeit DEFB2 (i.e., hBD2) is known to have a similar effect as DEFB123 (42). The inhibition of LPS and the blocking of TNF-␣ was also reported for the ␣-helical peptide MBI-28 (43), which is in the same MW range. In addition, the structurally unrelated cathelicidin CAP18/LL-37 shows similar behavior (33).…”
Section: Discussionmentioning
confidence: 79%
“…Cationic peptide binding to lipopolysaccharide has been well documented and has been related to a number of structural features contained within the peptide itself (16)(17)(18)36,(51)(52)(53)(54). Although specific charge groups and overall length of the peptide have been shown to be essential in the lipopolysaccharide-peptide binding interaction (11,12,15,55), increasing evidence is mounting which suggests that even small or shortened peptides (< 15 mers) retain significant lipopolysaccharide binding and immunomodulatory function (13,15,56).…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple lipopolysaccharide effects have been reported to be obtunded by various types of anti-microbial peptides (16)(17)(18)36,(52)(53)(54)57), little is known about the effects on E-selectin expression or hemagglutination. The present study also showed that the decapeptide KSL-W, throughout a wide concentration range (25-200 lg/mL) was able to obtund the lipopolysaccharide-induced expression of E-selectin in human umbilical vein endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several synthetic cationic antimicrobial peptides have been shown to block the LPS-and LTA-stimulated production of proinflammatory cytokines (e.g. TNF-a) by macrophages (Gough et al, 1996;Scott et al, 1999aScott et al, , 2000a. Dahlberg et al (1996) and Dankesreiter et al (2000) demonstrated that cationic antimicrobial peptides derived from various endotoxin-neutralizing proteins inhibited TNF-a release from LPS-stimulated macrophages.…”
Section: Neutralization Of Proinflammatory Bacterial Factors By Intermentioning
confidence: 99%
“…Furthermore, Dahlberg et al (1996) and Dankesreiter et al (2000) showed that cationic peptides decreased plasma TNF-a levels in mice infected with Escherichia coli. Gough et al (1996) reported that the cationic peptide CEMA reduced the LPS-induced circulating TNF-a in a mouse model of lethal endotoxic shock. A similar effect was reported with the human antimicrobial peptide LL-37 (Scott et al, 2002).…”
Section: Direct Anti-inflammatory Effect On Host Cellsmentioning
confidence: 99%